2023
DOI: 10.3390/cancers15102760
|View full text |Cite
|
Sign up to set email alerts
|

Perifocal Zone of Brain Gliomas: Application of Diffusion Kurtosis and Perfusion MRI Values for Tumor Invasion Border Determination

Abstract: (1) Purpose: To determine the borders of malignant gliomas with diffusion kurtosis and perfusion MRI biomarkers. (2) Methods: In 50 high-grade glioma patients, diffusion kurtosis and pseudo-continuous arterial spin labeling (pCASL) cerebral blood flow (CBF) values were determined in contrast-enhancing area, in perifocal infiltrative edema zone, in the normal-appearing peritumoral white matter of the affected cerebral hemisphere, and in the unaffected contralateral hemisphere. Neuronavigation-guided biopsy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Conversely, mere WM fiber displacement is suspected in cases where FA reduction is less than 25%. One possible solution to the poor differentiation of glioma infiltration from surrounding edema is represented in the study by Zakharova and colleagues [ 193 ], who analyzed 50 cases of high-grade glioma and showed that diffusion kurtosis MRI biomarkers pinpointed structural tissue alterations in the brain tissue surrounding the tumor masses, delineating the invasive tumor borders in otherwise normally-appearing white matter. Moreover, Ruggiero and colleagues [ 194 ] conducted a preclinical evaluation of fast-field cycling nuclear magnetic resonance (FFC-NMR) and found that T1-relaxation at very low magnetic field through this sequence can successfully discern between proliferating and invasive/migrating glioma tissue, highlighting the promise of low-magnetic field relaxometry for future implementation in glioma patients.…”
Section: Therapeutic Targets Of Glioma Invasionmentioning
confidence: 99%
“…Conversely, mere WM fiber displacement is suspected in cases where FA reduction is less than 25%. One possible solution to the poor differentiation of glioma infiltration from surrounding edema is represented in the study by Zakharova and colleagues [ 193 ], who analyzed 50 cases of high-grade glioma and showed that diffusion kurtosis MRI biomarkers pinpointed structural tissue alterations in the brain tissue surrounding the tumor masses, delineating the invasive tumor borders in otherwise normally-appearing white matter. Moreover, Ruggiero and colleagues [ 194 ] conducted a preclinical evaluation of fast-field cycling nuclear magnetic resonance (FFC-NMR) and found that T1-relaxation at very low magnetic field through this sequence can successfully discern between proliferating and invasive/migrating glioma tissue, highlighting the promise of low-magnetic field relaxometry for future implementation in glioma patients.…”
Section: Therapeutic Targets Of Glioma Invasionmentioning
confidence: 99%
“…Therefore, a single-PLD approach is recommended as the clinical standard scanning protocol in the guideline published in 2015 ( 9 ). Although 2 seconds is the suggested PLD for the clinical adult population in this guideline, previous studies have employed various PLD protocols ( 9 , 17 - 19 ), and the commonly used PLDs in recent studies have ranged from 1.5 to 2.5 seconds ( 11 , 18 - 23 ). In addition, a guidance published in 2023 states that many studies and clinical experiences have shown that the 2015 consensus PLD of 1,800–2,000 ms may not be sufficient for all the labeled blood to arrive in the brain parenchyma ( 10 ).…”
Section: Introductionmentioning
confidence: 99%